Jack Worthing's Pursuit Of Love Reflected In Oscar Wilde's The Importance Of Being Earnest Play : An Individual Psychological Approach - Saputra, Adhityas Surya; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
This study is about Pursuit of Love. The problem of this study is to reveal how the pursuit of love in major character named Jack Worthing is pursuing his love reflected in The Importance of Being Earnest play created by Oscar Wilde. There are two objectives: the first is to analyze the play in term of structural elements and the second is to analyze the play based on Individual Psychological Approach. The object of the study is The Importance of Being Earnest play by Oscar Wilde. It used Individual Psychological Approach. This study belongs to qualitative research. In this research, there are two types of data, namely primary and secondary data source. The primary data source is the play and secondary data source is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in The Importance of Being Earnest play, Oscar Wilde formulate a unity form in which one element that supports the others and the whole elements reflect the theme of the play. Second, based on the individual psychological approach the result shows that Jack Worthing pursuing of love had been changed from Empty love to Romantic love.